Process method for coating modified positive electrode material with solid electrolyte

Through the process method of solid electrolyte coating modification, the problems of rough coating effect and ultra-thin coating control in the prior art are solved, and the performance of the positive electrode material and the safety and stability of lithium-ion batteries are significantly improved.

CN119447256APending Publication Date: 2025-02-14ZHONGKE RONNENG (YANCHENG) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411649354.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing coating modification methods have problems in coating effect and ultra-thin coating control, which limits the performance improvement of the cathode material.

Method used

The process method of solid electrolyte coating modification includes pretreatment of the positive electrode material, preparation of lithium aluminate sol, coating treatment, washing and drying, calcining treatment and post-treatment, and the composite coating of solid electrolyte and carbon material is formed. A uniform cladding.

Benefits of technology

It significantly improves the electronic conductivity, cycle stability and rate performance of the positive electrode material, improves the safety and stability of lithium-ion batteries, reduces production costs and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447256A_ABST
    Figure CN119447256A_ABST
Patent Text Reader

Abstract

The invention discloses a process method for coating a modified positive electrode material with a solid electrolyte. The process method specifically comprises the following steps: S1, pretreating the positive electrode material; s2, preparing lithium metaaluminate sol; s3, carrying out coating treatment; s4, washing and drying; s5, calcining treatment; s6, carrying out post-treatment; the invention relates to the technical field of battery materials. According to the process method for coating the modified positive electrode material with the solid electrolyte, through composite coating of the solid electrolyte and the carbon material, the electronic conductivity, the cycling stability and the rate capability of the positive electrode material are remarkably improved, and a solid electrolyte coating layer can effectively protect the positive electrode material and prevent the positive electrode material from being in direct contact with electrolyte; therefore, the safety and stability of the lithium ion battery are improved, the preparation method is simple and convenient to operate, easy to control and suitable for large-scale industrial production, the adopted materials are low in cost, no complex equipment is needed in the preparation process, the production cost is reduced, and both the organic solvent and the stabilizer used in the preparation process can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery materials, and in particular to a process for coating a modified positive electrode material with a solid electrolyte. Background Art

[0002] Lithium-ion batteries, commonly known as rocking chair batteries, are a general term for batteries with lithium-ion embedded compounds as positive electrode materials. They are a type of secondary battery that mainly relies on the movement of lithium ions between the positive and negative electrodes to work. Lithium-ion batteries are composed of positive and negative electrodes, electrolytes and separators, plus positive and negative leads, battery shells, safety devices, etc. During the charging and discharging process of lithium-ion batteries, Li+ is embedded and de-embedded back and forth between the two electrodes: when charging, Li+ is de-embedded from the positive electrode, embedded in the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; when discharging, the opposite is true. Mobile phones and laptops all use lithium-ion batteries, which are usually referred to as lithium batteries. As a power source, lithium-ion batteries are widely used in individual electronic equipment, submarines, torpedoes, and drones.

[0003] Lithium-ion battery is a new type of chemical power source developed in recent years. It has the characteristics of small size, light weight, high specific energy, no memory effect, and long cycle life. It has been widely used in mobile devices, electric vehicle energy and other fields. Electrode materials are the core and key materials of lithium-ion batteries. Their performance directly determines the specific energy, cycle life and load resistance of lithium-ion batteries. Therefore, the development of high-performance and high-cycle life lithium-ion battery positive electrode materials has always been the research focus of scientific researchers.

[0004] Coating modification is a protective method that uses materials with excellent physical and chemical properties to form a uniform coating layer on the surface of the target material particles. Studies have shown that positive electrode materials modified by solid electrolyte coating have high capacity, good rate performance and superior cycle performance. However, existing coating modification methods, such as high-energy ball milling and sol-gel methods, have problems such as rough coating effect and difficulty in controlling ultra-thin coating, which limits the performance improvement of positive electrode materials. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a process for coating a modified positive electrode material with a solid electrolyte, which solves the problems mentioned in the above background technology.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: a process for coating a modified positive electrode material with a solid electrolyte, specifically comprising the following steps:

[0007] S1. Pretreatment of positive electrode materials: Select the positive electrode materials collectively and perform surface activation treatment, with an ultrasonic frequency of 35-40kHz and a cleaning time of 30-36 minutes to remove surface impurities and increase surface roughness;

[0008] S2. Preparation of lithium aluminate sol: dissolving aluminum ethoxide and lithium nitrate in anhydrous ethanol at a molar ratio of 1:1.5 to ensure complete dissolution, adding ethanolamine as a stabilizer in an amount of 3% of the total volume of the sol to improve the stability and uniformity of the sol, stirring at room temperature for 36-48 hours to obtain a uniform and transparent lithium aluminate sol;

[0009] S3, coating treatment: the activated positive electrode material is evenly dispersed in the lithium aluminate sol, and the coating is ensured to be uniform by mechanical stirring at a stirring speed of 450-500 rpm for 1-2 hours. The mixture is placed in a polytetrafluoroethylene reactor and kept at a temperature of 150°C-160°C for 10-12 hours to allow the sol to form a uniform coating layer on the surface of the positive electrode material;

[0010] S4, washing and drying: the coated positive electrode material is separated by suction filtration, washed with anhydrous ethanol for 3-5 times, each washing time is 10-16 minutes to remove the unabsorbed sol and impurities, placed in a blast drying oven, and dried at 80°C-100°C for 4-8 hours to ensure the initial solidification of the coating layer and remove residual moisture and solvent;

[0011] S5. Calcination treatment: Place the dried positive electrode material in a high temperature furnace and calcine it at a temperature of 450°C-480°C for 4-6 hours, with a heating rate of 5°C / min and a cooling rate of 3°C / min. Take it out after naturally cooling to room temperature. After calcination, characterize the structure and morphology of the coating layer by scanning electron microscopy to ensure the uniformity and integrity of the coating layer.

[0012] S6. Post-processing: The calcined material is subjected to post-processing steps such as crushing and screening to remove excess particles and impurities, and finally a solid electrolyte-coated modified positive electrode material with uniform particle size and excellent performance is obtained.

[0013] Preferably, the positive electrode material collectively includes any one or a combination of at least two of ternary materials, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide or lithium-rich positive electrode materials.

[0014] Preferably, in S1, the positive electrode material is a LiNi_xCo_yMn_zO_2 series material, wherein x, y, z are molar fractions, and x+y+z=1, and its purity is not less than 98%.

[0015] Preferably, in S2, the solid content of the sol obtained is 20%, ensuring that the concentration of the sol is moderate to facilitate subsequent coating treatment.

[0016] Preferably, in S3, during the heat preservation process, the pressure in the reactor is ensured to be stable to avoid volatilization and loss of the sol.

[0017] Preferably, in S5, during the calcination process, the atmosphere in the furnace is air to ensure sufficient oxidation and crystallization of the coating layer, and the thickness of the solid electrolyte layer is 10-50 μm.

[0018] The present invention also provides a solid-state battery, comprising a solid electrolyte-coated modified positive electrode material obtained by the above preparation method.

[0019] Beneficial Effects

[0020] The present invention provides a process method for coating a modified positive electrode material with a solid electrolyte. Compared with the prior art, the process method has the following beneficial effects: the process method for coating a modified positive electrode material with a solid electrolyte specifically comprises the following steps: S1, pretreatment of positive electrode material; S2, preparation of lithium aluminate sol; S3, coating treatment; S4, washing and drying; S5, calcination treatment; S6, post-treatment; through the composite coating of solid electrolyte and carbon material, the electronic conductivity, cycle stability and rate performance of the positive electrode material are significantly improved, the solid electrolyte coating layer can effectively protect the positive electrode material and prevent it from directly contacting the electrolyte, thereby improving the safety and stability of the lithium ion battery, the preparation method is simple to operate, easy to control, suitable for large-scale industrial production, the material cost used is low, and no complex equipment is required in the preparation process, which reduces the production cost, and the organic solvent and stabilizer used in the preparation process can be recycled and reused, reducing environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] See also Figure 1 The present invention provides three technical solutions: a process for coating a modified positive electrode material with a solid electrolyte, specifically including the following embodiments:

[0024] Embodiment 1

[0025] S1. Pretreatment of positive electrode materials: Select the positive electrode materials collectively and perform surface activation treatment, with an ultrasonic frequency of 37kHz and a cleaning time of 33 minutes to remove surface impurities and increase surface roughness;

[0026] S2. Preparation of lithium aluminate sol: dissolving aluminum ethoxide and lithium nitrate in anhydrous ethanol at a molar ratio of 1:1.5 to ensure complete dissolution, adding ethanolamine as a stabilizer in an amount of 3% of the total volume of the sol to improve the stability and uniformity of the sol, stirring at room temperature for 42 hours to obtain a uniform and transparent lithium aluminate sol;

[0027] S3, coating treatment: the activated positive electrode material is evenly dispersed in the lithium aluminate sol, and the coating is ensured to be uniform by mechanical stirring, the stirring speed is 475 rpm, the stirring time is 1.5 hours, and the mixture is placed in a polytetrafluoroethylene reactor and kept warm at a temperature of 155° C. for 11 hours, so that the sol forms a uniform coating layer on the surface of the positive electrode material;

[0028] S4, washing and drying: the coated positive electrode material is separated by suction filtration, washed with anhydrous ethanol for 4 times, each washing time is 13 minutes, to remove the unabsorbed sol and impurities, placed in a blast drying oven, and dried at 90°C for 6 hours to ensure the initial solidification of the coating layer and remove residual moisture and solvent;

[0029] S5. Calcination treatment: The dried positive electrode material is placed in a high-temperature furnace and calcined at 475°C for 5 hours, with a heating rate of 5°C / min and a cooling rate of 3°C / min. It is naturally cooled to room temperature and then taken out. After calcination, the structure and morphology of the coating layer are characterized by scanning electron microscopy to ensure the uniformity and integrity of the coating layer.

[0030] S6. Post-processing: The calcined material is subjected to post-processing steps such as crushing and screening to remove excess particles and impurities, and finally a solid electrolyte-coated modified positive electrode material with uniform particle size and excellent performance is obtained.

[0031] Embodiment 2

[0032] S1. Pretreatment of positive electrode materials: Select the positive electrode materials collectively and perform surface activation treatment, with an ultrasonic frequency of 35kHz and a cleaning time of 30 minutes to remove surface impurities and increase surface roughness;

[0033] S2. Preparation of lithium aluminate sol: dissolving aluminum ethoxide and lithium nitrate in anhydrous ethanol at a molar ratio of 1:1.5 to ensure complete dissolution, adding ethanolamine as a stabilizer in an amount of 3% of the total volume of the sol to improve the stability and uniformity of the sol, stirring at room temperature for 36 hours to obtain a uniform and transparent lithium aluminate sol;

[0034] S3, coating treatment: the activated positive electrode material is evenly dispersed in the lithium aluminate sol, and the coating is ensured to be uniform by mechanical stirring at a stirring speed of 450 rpm for 1 hour. The mixture is placed in a polytetrafluoroethylene reactor and kept at 150° C. for 10 hours to allow the sol to form a uniform coating layer on the surface of the positive electrode material;

[0035] S4, washing and drying: the coated positive electrode material is separated by suction filtration, washed with anhydrous ethanol for 3 times, each washing time is 10 minutes, to remove the unabsorbed sol and impurities, placed in a blast drying oven, and dried at 80°C for 4 hours to ensure the initial solidification of the coating layer and remove residual moisture and solvent;

[0036] S5. Calcination treatment: The dried positive electrode material is placed in a high-temperature furnace and calcined at 450°C for 4 hours at a heating rate of 5°C / min and a cooling rate of 3°C / min. The material is naturally cooled to room temperature and then taken out. After calcination, the structure and morphology of the coating layer are characterized by scanning electron microscopy to ensure the uniformity and integrity of the coating layer.

[0037] S6. Post-processing: The calcined material is subjected to post-processing steps such as crushing and screening to remove excess particles and impurities, and finally a solid electrolyte-coated modified positive electrode material with uniform particle size and excellent performance is obtained.

[0038] Embodiment 3

[0039] S1. Pretreatment of positive electrode materials: Select the positive electrode materials collectively and perform surface activation treatment, with an ultrasonic frequency of 40kHz and a cleaning time of 36 minutes to remove surface impurities and increase surface roughness;

[0040] S2. Preparation of lithium aluminate sol: dissolving aluminum ethoxide and lithium nitrate in anhydrous ethanol at a molar ratio of 1:1.5 to ensure complete dissolution, adding ethanolamine as a stabilizer in an amount of 3% of the total volume of the sol to improve the stability and uniformity of the sol, stirring at room temperature for 48 hours to obtain a uniform and transparent lithium aluminate sol;

[0041] S3, coating treatment: the activated positive electrode material is evenly dispersed in the lithium aluminate sol, and the coating is ensured to be uniform by mechanical stirring, the stirring speed is 500 rpm, the stirring time is 2 hours, the mixture is placed in a polytetrafluoroethylene reactor, and kept warm at a temperature of 160° C. for 12 hours, so that the sol forms a uniform coating layer on the surface of the positive electrode material;

[0042] S4, washing and drying: the coated positive electrode material is separated by suction filtration, washed with anhydrous ethanol for 5 times, each washing time is 16 minutes, to remove the unabsorbed sol and impurities, placed in a blast drying oven, and dried at 100°C for 8 hours to ensure the initial solidification of the coating layer and remove residual moisture and solvent;

[0043] S5. Calcination treatment: The dried positive electrode material is placed in a high-temperature furnace and calcined at 480°C for 6 hours at a heating rate of 5°C / min and a cooling rate of 3°C / min. The material is naturally cooled to room temperature and then taken out. After calcination, the structure and morphology of the coating layer are characterized by scanning electron microscopy to ensure the uniformity and integrity of the coating layer.

[0044] S6. Post-processing: The calcined material is subjected to post-processing steps such as crushing and screening to remove excess particles and impurities, and finally a solid electrolyte-coated modified positive electrode material with uniform particle size and excellent performance is obtained.

[0045] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0046] Effect Example

[0047] The solid-state batteries provided by Examples 1-3 and Comparative Example (conventional solid-state batteries on the market) were subjected to the following performance tests for capacity testing and cycle testing, and the test results are shown in the following table:

[0048]

[0049] It can be seen from the above table that the electronic conductivity, cycle stability and rate performance of the positive electrode material are significantly improved through the composite coating of the solid electrolyte and the carbon material. The solid electrolyte coating layer can effectively protect the positive electrode material and prevent it from direct contact with the electrolyte, thereby improving the safety and stability of the lithium-ion battery. The preparation method is simple to operate, easy to control, suitable for large-scale industrial production, the material cost used is low, and no complicated equipment is required in the preparation process, which reduces the production cost. The organic solvents and stabilizers used in the preparation process can be recycled and reused, reducing environmental pollution.

[0050] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0051] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for coating a modified positive electrode material with a solid electrolyte, characterized in that: The specific steps include: S1. Pretreatment of positive electrode materials: Select the positive electrode materials collectively and perform surface activation treatment, with an ultrasonic frequency of 35-40kHz and a cleaning time of 30-36 minutes to remove surface impurities and increase surface roughness; S2. Preparation of lithium aluminate sol: dissolving aluminum ethoxide and lithium nitrate in anhydrous ethanol at a molar ratio of 1:1.5 to ensure complete dissolution, adding ethanolamine as a stabilizer in an amount of 3% of the total volume of the sol to improve the stability and uniformity of the sol, stirring at room temperature for 36-48 hours to obtain a uniform and transparent lithium aluminate sol; S3, coating treatment: the activated positive electrode material is evenly dispersed in the lithium aluminate sol, and the coating is ensured to be uniform by mechanical stirring at a stirring speed of 450-500 rpm for 1-2 hours. The mixture is placed in a polytetrafluoroethylene reactor and kept at a temperature of 150°C-160°C for 10-12 hours to allow the sol to form a uniform coating layer on the surface of the positive electrode material; S4, washing and drying: the coated positive electrode material is separated by suction filtration, washed with anhydrous ethanol for 3-5 times, each washing time is 10-16 minutes to remove the unabsorbed sol and impurities, placed in a blast drying oven, and dried at 80°C-100°C for 4-8 hours to ensure the initial solidification of the coating layer and remove residual moisture and solvent; S5. Calcination treatment: Place the dried positive electrode material in a high temperature furnace and calcine it at a temperature of 450°C-480°C for 4-6 hours, with a heating rate of 5°C / min and a cooling rate of 3°C / min. Take it out after naturally cooling to room temperature. After calcination, characterize the structure and morphology of the coating layer by scanning electron microscopy to ensure the uniformity and integrity of the coating layer. S6. Post-processing: The calcined material is subjected to post-processing steps such as crushing and screening to remove excess particles and impurities, and finally a solid electrolyte-coated modified positive electrode material with uniform particle size and excellent performance is obtained.

2. The process for coating a modified positive electrode material with a solid electrolyte according to claim 1, characterized in that: The positive electrode material includes any one of a ternary material, lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide or a lithium-rich positive electrode material, or a combination of at least two thereof.

3. The process for coating a modified positive electrode material with a solid electrolyte according to claim 1, characterized in that: In the S1, the positive electrode material is a LiNi_xCo_yMn_zO_2 series material, wherein x, y, z are molar fractions, and x+y+z=1, and its purity is not less than 98%.

4. The process for coating a modified positive electrode material with a solid electrolyte according to claim 1, characterized in that: In the S2, the solid content of the obtained sol is 20%, which ensures that the concentration of the sol is moderate and is convenient for subsequent coating treatment.

5. The process for coating a modified positive electrode material with a solid electrolyte according to claim 1, characterized in that: In S3, during the heat preservation process, the pressure in the reactor is ensured to be stable to avoid volatilization and loss of the sol.

6. The process for coating a modified positive electrode material with a solid electrolyte according to claim 1, characterized in that: In S5, during the calcination process, the atmosphere in the furnace is air to ensure sufficient oxidation and crystallization of the coating layer. The thickness of the solid electrolyte layer is 10-50 μm.

7. A solid-state battery, characterized in that: The invention comprises a solid electrolyte coated modified positive electrode material obtained by the preparation method according to any one of claims 1 to 6.